Integrated solutions to improve wastewater quality in Mendoza and Santiago River Basin - Riera, Felix Sebastián (2024)
This study compares water quality governance in the Mendoza and Santiago River Basins, examining the impact of distinct policies and institutional structures in Argentina and Mexico. Despite differing climates, both basins share challenges such as sedimentation, agricultural runoff, and industrial discharges. We evaluate the impact of recent legislative reforms, highlighting positive outcomes in Mendoza, whereas Santiago faces institutional challenges. This research underscores the need for integrated solutions to address basin-specific challenges, including legislative reforms, stakeholder engagement, and innovative monitoring.